Slurry erosion behavior of destabilized and deep cryogenically treated Cr-Mn-Cu white cast irons - Gupta S.; Khandelwal A.; Ghose A.K.; Chakrabarty I. (My University, 2025)
The effects of destabilization treatment and destabilization followed by cryogenic treatment have been evaluated on the microstructural evolution and sand-water slurry erosion behavior of Cr-Mn-Cu white cast irons. The phase transformations after the destabilization and cryotreatment have been characterized by bulk hardness measurement, optical and scanning electron microscopy, x-ray diffraction analysis. The static corrosion rate has been measured in tap water (with pH=7) and the erosion-corrosion behavior has been studied by slurry pot tester using sand-water slurry. The test results indicate that the cryogenic treatment has a significant effect in minimizing the as-cast retained austenite content and transforming into martensitic and bainitic matrix embedded with ultra-fine M7C3 alloy carbides. In contrast, by conventional destabilization treatment retained austenite in the matrix are not fully eliminated. The slurry erosive wear resistance has been compared with reference to destabilized and cryotreated high chromium iron samples which are commonly employed for such applications. The cryotreated Cr-Mn-Cu irons have exhibited a comparable erosive wear performance to those of high chromium irons. Higher hardness combined with improved corrosion resistance result in better slurry erosion resistance. © 2016 Published by Faculty of Engineering.